Favorable long-term outcomes of autoimmune nodopathy with mycophenolate mofetil - Young Gi Min; Woohee Ju; Jung-Joon Sung; Jung-Joon Sung; Jung-Joon Sung; Jung-Joon Sung (Frontiers in Neurology)
Autoimmune nodopathy (AN) is a rare immune-mediated neuropathy characterized by autoantibodies against nodal or paranodal proteins. Patients with AN generally respond poorly to immunoglobulin therapy, and as a newly defined condition, there are currently no established treatment guidelines. Although rituximab shows potential as a therapeutic option, its high cost, limited availability, and the need for infusion monitoring hinder its use as a first-line treatment in many countries. In this report, we identified AN antibodies in five of 106 serum samples (4.7%) prospectively collected from patients initially diagnosed with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP): anti-neurofascin 155 (NF155) in 2 patients, anti-contactin-1 (CNTN1) in 1, anti-contactin associated protein 1 (CASPR1), and anti-NF186/140 in 1. Notably, we observed favorable long-term outcomes in these patients following treatment with mycophenolate mofetil (MMF) and corticosteroids. Given that these patients had not responded to immunoglobulin therapy and/or experienced relapses with corticosteroid monotherapy in their prior episodes, we propose MMF as a cost-effective treatment strategy for AN.